Comparative analysis of salmonella typhi by rRNA gene restriction and phage typing - Thong, Kwai Lin; Altwegg, M.; Pang, T. (2000)
Phage typing and ribotyping were used to analyze 19 isolates of Salmonella typhi from sporadic cases and two outbreaks of typhoid fever in Malaysia in 1987 and 1990. The two outbreaks were associated with phage types D1 and E1 in Penang and Alor Setar respectively, and phage types D1, E1 and A (with 3 untypeable isolates) were present among the sporadic cases. Ribotyping detected 14 ribotypes among the 19 isolates thus establishing its higher discriminative capacity compared to phage typing. The outbreak isolates were more homogeneous by ribotyping and the data also suggested that one outbreak was propagated, multi-focal in nature (Penang) while another was a point- source traceable to a single event (Alor Setar).